Efektifitas Penggunaan Media KIE Berbasis Mobile Apps Untuk Meningkatkan Pengetahuan Remaja Putri Tentang Menarche Di SMP 1 Campaka : Effectiveness of Using Mobile Apps-Based IEC Media to Increase Young Women's Knowledge About Menarche at SMP 1 Campaka - Karlina, Rimba (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Menarche is a process of growth of women into adulthood. This lack of knowledge about menarche causes adolescents to become taboo and even embarrassed to know what menarche is. The importance of this information and educational media is so that young women have good knowledge about menarche. The purpose of this study was to determine the effect of menarche education based on mobile apps to increase young women knowledge about menarche at SMP 1 Campaka in 2023. Methods: This research is a pre-experimental study with a one-group pre-test and post-test design. Research activities were conducted from March to April 2023. The population in this study were all young girls at SMP 1 Campaka 1 in 2023. The sample in this study was 62 young women. Respondents in this study were 62 young women at SMP 1 Campaka. Results: The results of this study found that there were differences in pre-test and post-test values ​​where the average pre-test value was 51,18 and the average post-test value was 73,85 p-value = 0,000 < (0,05). Discussion: The conclusion in this study is that there, then the influence of menarche education based on mobile apps to increase young women's knowledge about menarche at SMP 1 Campaka in 2023.